Pelatihan PMR Sadar Thalassemia pada Kegiatan Jumbara XXV Kabupaten Banyumas - Lantip Rujito; Diyah Woro Dwi Lestari; Fitranto Arjadi; Dinar Faiza (Jurnal Pengabdian Pada Masyarakat, 2018)
TRAINING OF THALASSEMIA-AWARE PMR IN XXV JUMBARA EVENT OF BANYUMAS REGENCY. Thalassemia is a health condition that still needs treatment and serious attention for the Indonesian government. As part of the thalassemia belt, Indonesia must act immediately to prevent the addition of thalassemia patients in the future. One of the mass educations that can be done is by self-awareness movement among school students. Palang Merah Remaja (PMR) became a potential youth organization as the educator agent. Intense training and debriefing on them can be a superior program for prevention among school students. Students, in this case, the Red Cross Youth who are at the junior and senior high school level are potential cadres to spread the right information about thalassemia to their peers.